Africa ' s unfolding diet transformation: implications for agrifood system employment. Issue 2 (16th November 2015) - Tschirley, David L; Snyder, Jason; Dolislager, Michael; Reardon, Thomas; Haggblade, Steven; Goeb, Joseph; Traub, Lulama; Ejobi, Francis; Meyer, Ferdi
Abstract : Purpose: – The purpose of this paper is to understand how the unfolding diet transformation in East and Southern Africa is likely to influence the evolution of employment within its agrifood system (AFS) and between that system and the rest of the economy. To briefly consider implications for education and skill acquisition. Design/methodology/approach: – The authors link changing diets to employment structure. The authors then use alternative projections of diet change over 15- and 30-year intervals to develop scenarios on changes in employment structure. Findings: – As long as incomes in ESA continue to rise at levels near those of the past decade, the transformation of their economies is likely to advance dramatically. Key features will be: sharp decline in the share of the workforce engaged in farming even as absolute numbers rise modestly, sharp increase in the share engaged in non-farm segments of the AFS, and an even sharper increase in the share engaged outside the AFS. Within the AFS, food preparation away from home is likely to grow most rapidly, followed by food manufacturing, and finally by marketing, transport, and other AFS services. Resource booms in Mozambique and (potentially) Tanzania are the main factor that may change this pattern. Research limitations/implications: – Clarifying policy implications requires renewed research given the rapid changes in Africa over the past 15 years. Originality/value: – This is the first paper to explicitly link changing diets to changing employment within the AFS.